What kind of Democracy and what kind of Mass Media do we have today? - Voskarides, Sotos (My University, 2019)
The Athenian, direct, democracy was applied evolutionarily for about 140 years (from 462 BC to 322 BC in Attica) resulting in the creation of culturefor example, anything that is freely provided to all citizens and results in their well-being. In Athens, when Democracy was prevailing, justice, philosophy, theatre, poetry, games, applied arts etc. and the principles of all sciences, were available freely to all citizens for the first time. The modern "representative" (or parliamentary) Democracy differs greatly from direct Democracy. For this reason, as a practical development and an improved version of the representative Democracy, the participatory Democracy is preferred these days. In the last 200 years or so with the spread of typography and the global prevalence of the 3rd industrial revolution (electricity, electronics, telecommunications, information technology, internet, etc.) the media has emerged evolutionarily, which today, at the beginning of the 4th industrial re-startion (Robotics, artificial intelligence, virtual reality, nanotechnology, Blockchain, drones, 5G etc.) play a dominant role in people's everyday life. In today's age, of speed, of insufficient leisure as well as tranquility, peace, joy and happiness for too many people, and where human values, quality of life and also survival of the human race are in question, mainly due to the visible danger of the negative and perhaps non-reversible effects of climate change, one of the most imperative questions that afflict thinking people is 'what kind of Democracy and what kind of Mass Media prevail today'? Do the people (Demos) really prevail, that is, the opinion of the majority? And if so, how is that opinion shaped? Are citizens really informed or manipulated by Mass Media? Is Orwell and the followers of conspiracy theories increasingly verified? Do fake news, fake journalists, fake experts and fake representatives or fake city/ State leaders dominate?
Keywords: Democracy; Media; Corruption; Interplay; Dialogue